Learning to teach mathematics through inquiry: a case study of continuing professional development in Malta - Calleja, James (2019)
In the past decade, local policy documents envisage a shift towards more student-centred and inquiry-based pedagogies. At the same time, the OECD (2009) report shows that Maltese teachers, particularly those of mathematics, while exhibiting constructivist beliefs describe using teacher- centred practices. It appears that, rather than demonstrating unwillingness to adopt student-centred approaches to teaching, Maltese teachers are unprepared to take on the challenge. The provisions of CPD, which have also seen documents proposing the development of school-based learning communities, become crucial towards addressing this issue and hence in preparing teachers for this change. This study focuses on the design of a CPD programme aimed towards supporting teachers in learning to teach mathematics through inquiry (LTMI). LTMI, which offers participation in summer workshops followed by ongoing follow-up meetings, is based upon research-informed principles of effective CPD, namely: offering practice-based learning, the provision of CPD materials, a community of practice component and long-term engagement. In addition, to facilitate the shift to IBL and to make it meaningful to teachers, CPD is designed around four IBL features. This means that the IBL features being promoted as essential for student learning – a task-oriented approach, creating opportunities for collaborative learning, using purposeful questioning and shifting agency and responsibility onto learners – are integrated within the CPD experiences offered to teachers. While investigating the impact that the designed CPD has on teacher development and change towards more IBL practices, this research explores case studies that delve deep into the challenges that Maltese teachers face. Conducted over a period of 14 months, this study looks into contextual factors to explore how these influence the way teachers enact IBL. This study adopts a case study methodology and use five key research instruments to collect data about each case study: semi-structured interviews, teacher questionnaires, lesson observations, teacher lesson journals and a focus group discussion. These data sources were administered at different stages: before, during and at the end of teachers’ participation in LTMI. With this data, the research sought to identify how teachers interpret and enact IBL in their classrooms, the ways in which they structure their IBL lessons and the changes in beliefs and practices that take place over the course of the CPD programme. Data from this research show that teachers’ interpretation of IBL is context- specific and influenced by system restrictions, and the way they operationalise IBL is influenced by how students engage with and respond to the inquiry teaching practices that they offer. In the change process, teachers are likely to go through a phase where they adopt a discovery teaching approach. Moreover, teachers structure their lessons in atypical ways. This appears to be influenced by a number of factors but particularly the tasks they use. Modifications to lesson structure are found to be inevitable as teachers learn about ways of providing purposeful interventions to facilitate the learning process for their students. Over the course of LTMI, teachers also report changes towards more connectionist beliefs – these being more consistent with their inquiry practices. Teachers attribute changes in practice and learning about IBL implementation as emanating and enhanced by their ongoing engagement within a community of practice. The collegial, safe and informal setting contrasted with the isolated and restricting contexts of learning within teachers’ own schools. In supporting the enactment of reform, this thesis offers recommendations towards providing ‘just-in-time’ collaborative learning opportunities for teachers in supporting them with enabling change. Enabling change requires empowering teachers to become autonomous learners in creating their own professional workplace learning networks and assuming professional learning responsibilities.